2020
DOI: 10.3389/fphar.2020.01326
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin Promotes Cisplatin−Induced Apoptosis of Gastric Cancer In Vitro and In Vivo by Upregulating PTEN Expression

Abstract: As one of the most common malignant gastrointestinal tumors, gastric cancer (GC) has a high incidence and poor prognosis. Cisplatin (DDP) is often used as chemotherapy for advanced GC; however, the high incidence of drug resistance remains a problem. The use of several anti-tumor drugs as combined chemotherapy is an effective strategy. Hesperetin has anti-tumor ability via its pro-apoptotic effect on various human cancers, both in vitro and in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…In an in vivo and in vitro study, the results provided strong evidence that hesperidin enhances antitumor effects on gastric cancer by regulating PI3K/AKT signaling pathway through the upregulation of PTEN expression. In addition, a combinatory therapy of cisplatin with hesperidin could enhance the clinical outcome [120]. Additionally, luteolin can inhibit cellular proliferation by regulating PI3K, AKT and mTOR signaling pathways, which play a key role in the progression and development of gastric cancer [132].…”
Section: Cellular Proliferationmentioning
confidence: 99%
“…In an in vivo and in vitro study, the results provided strong evidence that hesperidin enhances antitumor effects on gastric cancer by regulating PI3K/AKT signaling pathway through the upregulation of PTEN expression. In addition, a combinatory therapy of cisplatin with hesperidin could enhance the clinical outcome [120]. Additionally, luteolin can inhibit cellular proliferation by regulating PI3K, AKT and mTOR signaling pathways, which play a key role in the progression and development of gastric cancer [132].…”
Section: Cellular Proliferationmentioning
confidence: 99%
“…In our study, both young and mature leaves having their own unique metabolites. Differential metabolite analysis showed that most of the 12 metabolites present only in mature leaves have anti-tumor, anti-cancer, antioxidant, anti-inflammatory, anti-osteoporotic, anti-allergy, and other effects, which have high development value ( Bernatova, 2018 ; Chen et al, 2020 ; García-Lafuente et al, 2009 ; He et al, 2020 ; Ke et al, 2019 ; Kim et al, 2004 ; Li et al, 2017 ; Wei et al, 2019 ; Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Limonin could induce apoptosis, thereby affecting the growth of SNU449 and HCT-15 tumor cells (Rahman et al, 2015). Hesperetin could promote cisplatininduced apoptosis in gastric cancer through upregulating the expression of tensin homolog (PTEN) (He et al, 2020). Naringin and its aglycone naringenin have shown anti-carcinogenic activities through cell signal transduction pathways in cancer (JAK-STAT pathway, PI3-kinase/Akt/ mTOR pathway, Notch pathway, NF-κB and cox-2 pathway, Wnt pathway, MAPK-ERK pathway, TGF-β pathway) (Memariani et al, 2020).…”
Section: The Potential Mechanism Of Elc Treatmentmentioning
confidence: 99%